2010
DOI: 10.1371/journal.pone.0009068
|View full text |Cite
|
Sign up to set email alerts
|

Replication, Pathogenesis and Transmission of Pandemic (H1N1) 2009 Virus in Non-Immune Pigs

Abstract: The declaration of the human influenza A pandemic (H1N1) 2009 (H1N1/09) raised important questions, including origin and host range [1], [2]. Two of the three pandemics in the last century resulted in the spread of virus to pigs (H1N1, 1918; H3N2, 1968) with subsequent independent establishment and evolution within swine worldwide [3]. A key public and veterinary health consideration in the context of the evolving pandemic is whether the H1N1/09 virus could become established in pig populations [4]. We perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
138
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(162 citation statements)
references
References 30 publications
(54 reference statements)
23
138
0
1
Order By: Relevance
“…Our study confirms that pigs are susceptible to either the swine or human 2009 pH1N1 isolates, as reported previously (5,25,55). In addition, we found that virus replication in pH1N1-infected and classical IA30 virus-infected pigs was similar, but pH1N1 induced clear symptoms in pigs while IA30 did not.…”
Section: Discussionsupporting
confidence: 92%
“…Our study confirms that pigs are susceptible to either the swine or human 2009 pH1N1 isolates, as reported previously (5,25,55). In addition, we found that virus replication in pH1N1-infected and classical IA30 virus-infected pigs was similar, but pH1N1 induced clear symptoms in pigs while IA30 did not.…”
Section: Discussionsupporting
confidence: 92%
“…In order to test the capability of the new virus to be established in swine population, an experimental infection and transmission studies were performed (3,16). The obtained results clearly demonstrated that pdm H1N1 2009 virus is entirely capable of becoming established in global pig populations.…”
Section: Introductionmentioning
confidence: 98%
“…More importantly, the three viruses had enhanced contact transmissibility in both pigs and guinea pigs. Their enhanced virulence and contact transmissibility were similar to that of the H1N1/2009 virus (38)(39)(40). Since the virulence and contact transmissibility were comparable between the L2, N9, and L18 viruses, these acquired traits were determined primarily by the five consensus mutations (PB1 A469T, PA I129T, NA N329D, NS1 N205K, and NEP T48N) found in all three virus species.…”
Section: Discussionmentioning
confidence: 80%